Evaluation of different intercropping systems for productivity and economics in maize (Zea mays L.) - Shri, Sonam; Jha, A.K.; Shirvastava, Arti (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif season 2011 under "All India Co-ordinated Research Project on Forage Crop" at Farm of Agriculture College, Jabalpur to evaluate different maize based intercropping system for productivity and economics ". The intercropping of maize with soybean, ricebean and cowpea with 1:1 and 1:2 ratio gave higher maize equivalent yield than sole crop. The intercropping of maize with soybean 1:2 ratio possessed the maximum energy interception, energy utilization, PAR interception, PAR utilization and also gave the higher LER 1.57 than other treatments. The intercropping of maize with soybean 1:2 ratio was more remunerative and gave maximum yield, net return and B:C ratio.